\(Pt\left(1\right)\): \(3mx-1=5m-x\) \(\Leftrightarrow\) \(3mx+x=5m+1\) \(\Leftrightarrow\) \(\left(3m+1\right)x=5m+1\) \(\Leftrightarrow\) \(x=\frac{5m+1}{3m+1}\)
\(Pt\left(2\right)\) : \(m-x=3mx+1\) \(\Leftrightarrow m-1=3mx+x\) \(\Leftrightarrow\) \(\left(3m+1\right)x=m-1\)\(\Leftrightarrow\) \(x=\frac{m-1}{3m+1}\)
Để \(pt\left(1\right)\) và \(pt\left(2\right)\) có cùng nghiệm thì \(\frac{5m+1}{3m-1}=\frac{m-1}{3m+1}\)\(\Leftrightarrow\)\(5m+1=m-1\)\(\Leftrightarrow\)\(4m=-2\Leftrightarrow m=-\frac{1}{2}\)
Đúng 0
Bình luận (0)